Underutilized fruits crops and technologies for meeting their market needs - Kamboj, Vikrant; Tripathi, Shailesh; Joshi, Udit; Tewari, Vatsala (Journal of Postharvest Technology, 2020)
Fruit crops are considered and categorized under protective food because of their richness in various phytochemicals minerals and vitamins. They are rich sources of certain soluble dietary fiber which reduces erratic bowel movements, aids in cholesterol and fats reduction from the body and helps in boosting the immune system. Underutilized crops may be termed as the crops, that are neither grown on a commercial or large scale nor are traded widely around the world. These crops fall under lesser recognized plant species in terms of research and marketing aspects but can be seen well adapting to wild and stress like conditions. Research worldwide researches have shown shreds of evidence of underutilized wild edible plants possessing great valuable nutritional value. Since ages, several underutilized indigenous fruit crops having medicinal properties are utilized in various indigenous medicinal systems like Ayurveda, Unani, and Homoeopathy. The popular processed products made from these fruit crops are jam, RTS, fruit drinks, chutneys, candies, pickles, squashes, concentrate, etc. These fruit crops are a rich source of vitamin C which has been proved as a boon in enhancing immunity in this COVID-19 pandemic times. These crops can even cure insomnia, scurvy, constipation hemorrhage, leucorrhea. anemia, stomach ache, and can be used as a cooling agent to reduce sun strokes ill effects. Underutilized fruit crops can even adapt to low input agriculture. More research and development efforts in these crops will certainly add substantially to food security and nutrition. There is a need to develop high yielding varieties, production and protection technologies, and post-harvest management practices for these crops. Better coordination among all the agencies involved in research, development, and promotion will help popularize these fruit crops.